The impact of climate change on water resources and food security in Indonesia - Rizal Akbar Aldyan (Journal of Law, Environmental and Justice, 2023)
The agricultural industry in Indonesia is facing a significant challenge in the form of climate change, particularly with regards to its impact on water resources. Climate change has various consequences, such as diminished precipitation, compromised water quality, and alterations in water availability. These outcomes pose significant risks to both food security and the long-term viability of agricultural output. The vulnerability of the water sector on Java Island is further intensified by factors such as population growth, land use changes, excessive utilization of water resources, and the expansion of infrastructure. The phenomenon of diminishing water discharge and alterations in water quality has emerged, posing a risk to water resources and substantial reservoirs. There is a pressing need for enhanced comprehension and proactive measures to effectively mitigate the repercussions of climate change on Indonesia's water resources.